In vivo acridine orange human spermatozoa staining—A new perspective for RNA detection and spermatozoa morphology evaluation. (24th August 2020) - Fucic, Aleksandra; Maric, Tihana; Vicic Bockor, Vedrana; Jezek, Davor
Abstract: Significant increases in male infertility and the still unresolved questions on the compatibility and interpretation of current methods in infertility diagnostics call for new protocols. Morphology, genome damage, RNA content and quantity are currently in practice as the major parameters in evaluation of sperm quality. However, results of various methods are not always in mutual concordance. In this study, in vivo acridine orange (AO) staining, which is presently in application in the estimation of genome damage in reticulocytes, was adjusted for spermatozoa staining. Ten men suffering from oligoasthenoteratozoospermia (OAT) and 10 healthy fertile men were analysed using in vivo AO staining. Microscopic analysis was performed by fluorescent and confocal fluorescent microscopy. Our results show that this method preserves spermatozoa membranes, which enables new insight into spermatozoa genome damage, RNA content in residual cytoplasm, damage of neck area with mitochondrion and tail pathology. The introduced method explains the difference between results of sperm DNA fragmentation assay and the globally used AO staining and opens new options for the development of automated systems. In conclusion, the results of our study offer (a) an innovative approach to the analysis of spermatozoa pathology, (b) enable localization and quantification of RNA in residual cytoplasm, (c) a significant contribution to research of aetiology of infertility in men, (d) open new perspectives for the automatization of sperm quality estimation and (e) improve the personalized approach in the selection of in vitro fertilization protocols.